The Influence of Shyness on the Scanning of Own- and Other-Race Faces in Adults - Wang, Qiandong (Public Library of Science, 2012)
The current study explored the relationship between shyness and face scanning patterns for own- and other-race faces in adults. Participants completed a shyness inventory and a face recognition task in which their eye movements were recorded by a Tobii 1750 eye tracker. We found that: (1) Participants’ shyness scores were negatively correlated with the fixation proportion on the eyes, regardless of the race of face they viewed. The shyer the participants were, the less time they spent fixating on the eye region; (2) High shyness participants tended to fixate significantly more than low shyness participants on the regions just below the eyes as if to avoid direct eye contact; (3) When participants were recognizing own-race faces, their shyness scores were positively correlated with the normalized criterion. The shyer they were, the more apt they were to judge the faces as novel, regardless of whether they were target or foil faces. The present results support an avoidance hypothesis of shyness, suggesting that shy individuals tend to avoid directly fixating on others’ eyes, regardless of face race.